Collaborative Governance in Accelerating Stunting Reduction through Corporate Social Responsibility - Hanny Rizky Wasiat, Safira; Valiant Salomo, Roy (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to explore collaborative governance in accelerating the reduction of stunting through Corporate Social Responsibility (CSR) programs in Warakas Village, North Jakarta. The Ketapang Kuning program, a CSR initiative, successfully reduced the stunting rate from 19.3% to 12% in 2022. This study employs a qualitative approach with data collection techniques that include field studies and literature reviews. The results indicate that collaboration between the private sector, government, and community is crucial in addressing stunting issues. Key factors supporting the success of this program include power-resource-knowledge asymmetries such as knowledge, managerial capabilities, and financial resources from the business sector, as well as incentives to participate in the form of internal and external motivations like rewards, and collective facilitative leadership and transparency. The discussion of this research emphasizes the importance of corporate social responsibility (CSR) in reducing stunting and how effective collaboration between various parties can produce significant impacts. The collaboration between the government and the private sector, as demonstrated by PT. PLN IP Priok PGU, serves as a concrete example of how human resources and available funds can be optimally utilized to achieve common goals in stunting reduction.